Disseminated coelomic xanthogranulomatosis in eclectus parrots (Eclectus roratus) and budgerigars (Melopsittacus undulatus). Issue 1 (January 2022) - Donovan, Taryn A.; Garner, Michael M.; Phalen, David; Reavill, Drury; Monette, Sebastien; Le Roux, Alexandre B.; Hanson, Melissa; Chen, Sue; Brown, Cyndi; Echeverri, Catalina; Quesenberry, Katherine
Xanthogranulomatosis is an inflammatory lesion characterized by lipid-containing macrophages, extracellular lipid, hemorrhage, and necrosis. We describe disseminated intracoelomic xanthogranulomatosis in 5 eclectus parrots ( Eclectus roratus ) and 2 budgerigars ( Melopsittacus undulatus ). Postmortem, clinicopathologic, and historical case material was reviewed. Ages ranged from 3 to 24 years; there were 5 males and 2 females. Table food was included in the diet of 3/5 cases, and animal products were included in 2/3 cases. Common clinicopathologic abnormalities included leukocytosis (4/5 cases) and elevated concentrations of bile acids (3/4 cases) and cholesterol within 6 months prior to death (2/4 cases). At postmortem examination, all 7 birds had grossly visible, irregular, soft, tan to yellow, amorphous plaques distributed on the surfaces of the viscera and body wall. Histologic evaluation and oil red O stain revealed xanthogranulomatous inflammation with phagocytized and extracellular lipid, necrosis, cholesterol clefts, fibrosis, and mineralization. Infectious agents were not identified with special stains in all cases. Concurrent hepatobiliary disease was present in 6/7 cases, and 6/7 had lipid accumulation within the parenchyma of various visceral organs. Five cases had atherosclerosis of great vessels. We describe a unique form of disseminated coelomic xanthogranulomatosis in 2 psittacine species. This condition should be recognized as a differential diagnosis in cases of disseminated coelomic mass formation and coelomic distension in psittacine birds, particularly in eclectus parrots and budgerigars.